Genome Rearrangements Associated with Aberrant Telomere Maintenance - Bhargava, Ragini (Curr Opin Genet Dev, 2020)
There is unequivocal evidence that telomeres are critical for cellular homeostasis and that telomere dysfunction can elicit genome instability and potentially initiate events that culminate in cancer. Mounting evidence points to telomeres having a critical role in driving local and systemic structural rearrangements that drive cancer. These include the classical “breakage-fusion-bridg” (BFB) cycles and more recently identified genome re-shaping events like kataegis and chromothripsis. In this brief review, we outline the established and most recent advances describing the roles that telomere dysfunction has in the origin of these catastrophic genome rearrangements. We discuss how local and systemic structural rearrangements enable telomere length maintenance, by either telomerase or the alternative lengthening of telomeres, that is essential to sustain cancer cell proliferation.